Recurrent Exposure of XEN Gel Stent Implant and Conjunctival Erosion. Issue 3 (March 2019) - Arnould, Louis; Theillac, Vincent; Moran, Sarah; Gatinel, Damien; Grise-Dulac, Alice
Abstract : Purpose: The purpose of this study was to report a case of recurrent conjunctival erosion and XEN Gel Stent exposure after implantation in a primary open-angle glaucoma patient. Minimally invasive glaucoma surgery (MIGS) is a new approach in glaucoma surgery, and there is a lack of published data with regard to the management of postoperative ocular surface complications. Methods: This is a case report of a patient with a persistent corneal erosion after XEN Gel Stent implantation. A standalone MIGS surgery was planned for both eyes in this case of refractory glaucoma. Despite a first surgical revision, the patient was suffering from a chronic leaking bleb, an exposed XEN Gel Stent, and severe hypotonia in the left eye. Results: A free conjunctival autografting technique covered with a complementary amniotic membrane graft was performed under local anesthesia. One month following bleb revision, the intraocular pressure was 13 mm Hg on medical treatment, and slit-lamp examination showed a well-formed moderate bleb with no leakage. Conclusions: This is the first described case of the use of a free conjunctival autograft to treat a persistently leaking bleb after XEN Gel Stent implantation. This case highlights the potential complication of conjunctival erosion due to XEN Gel Stent implantation. It emphasizes the management of complicated filtration blebs after MIGS surgery.